Lock & key : the secrets of locking things up, in, and out - Tchudi, Stephen, 1942- (New York : Charles Scribner's Sons ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1993)
Describes the development and uses of different kinds of locks, relates stories about important locks in history, and discusses the meanings that the words "lock" and "key" have taken on in our language.
Includes bibliographical references (p. 107-108) and index.
Keywords: Locks and keys -- History -- Juvenile literature; Locks and keys -- History